Colonial America Today: U.S. Empire and the Political Status of Native American Nations. (April 2019) - Bacon, J. M.; Norton, Matthew
Abstract: The article systematically assesses U.S.-Native relations today and their historical foundations in light of a narrow, empirical definition of colonial empire. Examining three core elements of colonial empire—the formal impairment of sovereignty, the intensive practical impairment of sovereignty through practices of governance and administration, and the continuing otherness of the dominated and dominant groups—we compare contemporary U.S.-Native political relations to canonical instances of formal colonial indirect rule empires. Based on this analysis, we argue that the United States today is a paradigmatic case of formal colonial empire in the narrow, traditional sense, one that should be better integrated into the comparative, historical, and sociological study of such formal empires. Furthermore, this prominent contemporary case stands against the idea that the era of formal colonial empire is over.